2012
DOI: 10.1371/journal.pone.0033411
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk in Diabetic Patients Treated with Metformin: A Systematic Review and Meta-analysis

Abstract: BackgroundA growing body of evidence has suggested that metformin potentially reduces the risk of cancer. Our objective was to enhance the precision of estimates of the effect of metformin on the risk of any-site and site-specific cancers in patients with diabetes.Methods/Principal FindingsWe performed a search of MEDLINE, EMBASE, ISI Web of Science, Cochrane Library, and ClinicalTrials.gov for pertinent articles published as of October 12, 2011, and included them in a systematic review and meta-analysis. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
353
1
20

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 494 publications
(391 citation statements)
references
References 97 publications
(126 reference statements)
17
353
1
20
Order By: Relevance
“…Extensive preclinical data supports the efficacy of metformin as an antineoplastic agent [67], inhibiting cancer cell proliferation in gastric, medullary thyroid, breast, and pancreatic cancers [68][69][70][71]. Epidemiologic studies have also shown a decreased risk of cancer incidence and mortality from metformin use in diabetics [72], and clinical trials elucidating metformin's effect on head and neck squamous cell carcinoma are already underway. Further studies assessing its role in thyroid cancer, among other cancers, are needed to support these claims.…”
Section: Clinical Applications Of Thyroid Cancer Metabolism and Futurmentioning
confidence: 96%
“…Extensive preclinical data supports the efficacy of metformin as an antineoplastic agent [67], inhibiting cancer cell proliferation in gastric, medullary thyroid, breast, and pancreatic cancers [68][69][70][71]. Epidemiologic studies have also shown a decreased risk of cancer incidence and mortality from metformin use in diabetics [72], and clinical trials elucidating metformin's effect on head and neck squamous cell carcinoma are already underway. Further studies assessing its role in thyroid cancer, among other cancers, are needed to support these claims.…”
Section: Clinical Applications Of Thyroid Cancer Metabolism and Futurmentioning
confidence: 96%
“…However, other studies did not detect the relationship between metformin treatment and CRC risk among diabetes (Yang et al 2004;Bodmer et al 2012;Cardel et al 2014;Tsilidis et al 2014;Xu et al 2014). Several meta-analyses were conducted to evaluate the relationship, while the tissue still remains controversial (Decensi et al 2010;Zhang et al 2011;Noto et al 2012;Soranna et al 2012;Gandini et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Of recent interest is the potential repurposing of metformin, an oral insulinsensitizer used as first-line treatment for Type 2 diabetes (DM2). Specifically, there is now interest in validating the several meta-analyses indicating the usefulness of metformin in cancer therapy and/or prevention [1][2][3]. Indeed, cytotoxic effects of metformin in many cancer cell lines has been demonstrated [4,5].…”
Section: Introductionmentioning
confidence: 99%